2019
DOI: 10.31788/rjc.2019.1215059
|View full text |Cite
|
Sign up to set email alerts
|

ANTIDIABETIC ACTIVITY OF OKRA (Abelmoschus esculentus L.) FRUIT EXTRACT

Abstract: Diabetes mellitus is a heterogeneous group of disorders characterized by increasing blood glucose level caused by lack of insulin hormone. One of the plants that were often used as traditional medicine for diabetes in Indonesia was okra (Abelmoschus esculentus L.) fruit. The aim of this research was to evaluate the antidiabetes activity of okra fruit extract. The study was divided into several steps: a preliminary study of anthyperglycemia of okra fruit after glucose, sucrose, and amylum administration; antidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Earlier, the antidiabetic activity of okra has been reported by Ahmad et al (2016), and they found that aqueous extract of okra at different increasing concentrations (50,100,150,200, and 250 µg/mL) has reportedly increased the inhibition for both percentage of α-amylase and α-glucosidase enzyme. This reported result was consistent with our results [45,46]. In both the assays, the mucilage polymer showed significant results, indicating that OMB has potential, and it needs to be further explored for toxicity studies and clinical trials, and by virtue of that, it could become an important anti-diabetic agent.…”
Section: Antidiabetic Activitysupporting
confidence: 92%
“…Earlier, the antidiabetic activity of okra has been reported by Ahmad et al (2016), and they found that aqueous extract of okra at different increasing concentrations (50,100,150,200, and 250 µg/mL) has reportedly increased the inhibition for both percentage of α-amylase and α-glucosidase enzyme. This reported result was consistent with our results [45,46]. In both the assays, the mucilage polymer showed significant results, indicating that OMB has potential, and it needs to be further explored for toxicity studies and clinical trials, and by virtue of that, it could become an important anti-diabetic agent.…”
Section: Antidiabetic Activitysupporting
confidence: 92%
“…27 Mice model observed the antidiabetic activity with the mechanism of action by increasing insulin secretion, increasing insulin sensitivity, and inhibiting carbohydrate absorption in the intestine bythe exctract of ladies finger with a dose of 50 mg/kg body weight but couldn't inhibit alpha-glucosidase and alpha-amylase enzyme. 28 In contrast, one study found that co administration of water soluble fraction of ladies finger with metformin significantly reduced the metformin absorption. 29 With regard to fenugreek seeds water, our study is consistent with a clinical trial which found that after taking fenugreek seeds water for 8 weeks had significant reduction in FBS among type 2 diabetes.…”
Section: Discussionmentioning
confidence: 95%
“…According to the report of Hu et al (2014) the ladies finger polysaccharide has been possesses hepatoprotective, besides antidiabetic (Aligita et al, 2019). Additionally, antidiabetic and antihyperlipidemic activities reported in rats.…”
Section: Blood Biochemistrymentioning
confidence: 99%
“…According to previous study published by Sabitha et al (2011Sabitha et al ( , 2012 the diabetic rats that fed okra peel and seed powder at 100 and 200 mg.kg-1 dose, exhibited a significant decrease in sera glucose levels and a boost in body weight as the comparison with untreated, diabetic rats. Furthermore, the antidiabetic activity of the okra fruit extract with a dose of 50 mg. kg -1 BW, with the mechanism of action by increasing insulin secretion and rising insulin sensitivity, as well as inhibited carbohydrate absorption in the intestine (Aligita et al, 2019).…”
Section: Blood Biochemistrymentioning
confidence: 99%